The Effectiveness of CSR Communication in Telecommunications Networks: A Case Study of Indosat Ooredoo Hutchison - Diah Kusuma Dewi; Devi Suryaningsih; Maria Ariesta Utha (International Journal Labs, 2025)
In the context of the increasingly competitive and accountability-demanding telecommunications industry, Corporate Social Responsibility (CSR) communication is a crucial element in building trust and social legitimacy. This study explores and evaluates the perceived effectiveness of Corporate Social Responsibility (CSR) communication strategies implemented by Indosat Ooredoo Hutchison (IOH), particularly during its critical post-merger period. Adopting a qualitative, multi-method approach using triangulation, the research involved internal and external stakeholder surveys alongside netnographic observation of social media responses. Findings indicate that IOH's CSR communication is generally perceived as effective: most external stakeholders (78%) found the information transparent and easy to understand. Social media, with Instagram (45%) and Facebook (25%) as leading platforms, proved highly influential for CSR content. While message credibility was noted, service-related complaints often undermined perceived sincerity. Most external respondents (73%) reported an improved brand perception due to CSR initiatives. However, internal stakeholders expressed a strong desire for deeper involvement in CSR planning. Practically, the study suggests optimizing communication platforms and diversifying content to strengthen legitimacy and trust in this highly scrutinized sector.